Nir2 crystal structures reveal a phosphatidic acid–sensing mechanism at ER–PM contact sites - Dongyoung Kim; Seowhang Lee; Youngsoo Jun; Changwook Lee (Proceedings of the National Academy of Sciences, 2025)
Agonist-induced activation of phosphoinositide-specific phospholipase C (PLC) converts phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ] to diacylglycerol (DAG) at the inner leaflet of the plasma membrane (PM). DAG can be enzymatically transformed into phosphatidic acid (PA) and accumulated at the PM. PYK2 N-terminal domain-interacting receptor 2 (Nir2) mediates the formation of ER–PM membrane contact sites (MCSs) by specifically recognizing PA at the PM and directly interacting with ER membrane protein vesicle-associated membrane protein-associated proteins (VAPs). The N-terminal phosphatidylinositol transfer protein domain of Nir2 facilitates PI/PA exchange at ER–PM MCSs to maintain PI and PA levels. Here, we reveal the mechanisms by which Nir2 senses phosphatidic acid (PA) and associates with membranes, based on three crystal structures of its C-terminal Lipin/Ned1/Smp2 (LNS2) domain bound to PA, the diphenylalanine [FF]–containing acidic tract (FFAT) motif complexed with vesicle-associated membrane protein–associated protein B/C (VAPB), and the Asp-Asp-His-Asp (DDHD) domain. The C-terminal LNS2 domain of Nir2 directly interacts with the phosphate in the headgroup of PA via hydrogen bonds involving S1025, T1065, K1103, and K1126. Formation of a salt bridge between E355 in Nir2 and R55 in VAPB is essential for Nir2 FFAT–VAPB interaction. The central DDHD domain of Nir2 forms a twofold symmetric dimer, and this self-association contributes to stable and tight membrane association. These findings reveal how Nir2-mediated ER–PM MCS formation maintains continued PI(4,5)P 2 -dependent PLC signaling.